Oil Pollution in Nigerian and the Issue of Human Rights of the Victims - Adams Adoga-Ikong; Patience Tah Besong (Program Studi Sosiologi, 2020)
One of the major environmental problems in Nigeria today is that of oil pollution in the oil producing areas of the country. The country has suffered environmental degradation as a result of the oil pollution in the last of five (5) decades. The causes of this oil pollution were oil spillage, gas flaring, and effluent discharge from the refineries. These have caused untold hardships on the people living close or near the oil installations or facilities and have affected their lives, wellbeing, means of livelihood and the environment generally. Oil pollution activities have also affected their right to good and decent life, human dignity and lots. Unfortunately, the victims seem to be unable to assert their human right. The reason being that there are no constitutional and statutory provisions on environmental right to those who suffer such except common law remedies such as negligence, nuisance etc which require strict and technical proofs. The constitutional provision on the right to environment in chapter II of the 1999 constitution is lax and not justifiable. The only available redress is recourse to the human rights in Nigeria isa recourse to chapter 4 of the Constitution. This situation has caused untold hardship on the people because they have no way of seeking redress when their rights are being violated. As a result of this ugly development, this work has recommended that Nigeria should borrow a leaf from other jurisdictions such as India, South Africa etc. where human rights and environmental rights are practiced together.